Comparative Analysis of the Effectiveness of Steam versus Water Injection Techniques for NOx Reduction in an Intercooled Combined Cycle Gas Turbine - Agbadede, Roupa; Kainga, Biweri; Allison, Isaiah (Current Approaches in Engineering Research and Technology Vol. 10, 2024)
NOx emissions from gas turbine combustion processes pose significant risks to both human health and the environment. Gas turbine manufacturers and users have implemented various methods to reduce these emissions. Recently, different methods have been employed to reduce NOx emissions generated from gas turbine combustion processes. Both water and steam injection techniques have been described as means of reducing NOx emissions. However, there is an ongoing debate and some misconceptions regarding which of these two approaches is more effective in NOx reduction. This study presents a comparative analysis of the effectiveness of steam versus water injection techniques for NOx reduction in an intercooled combined cycle gas turbine. GasTurb simulation software was used to simulate the effectiveness of both steam and water injection on NOx reductions in an intercooled combined cycle gas turbine engine. The intercooled combined cycle gas turbine engine selected for this study was derived from the LMS100 gas turbine. This engine was chosen due to its capability to deliver a substantial amount of electricity to meet energy demands and its ability to operate efficiently under varying climate conditions. Simulations for steam-to-fuel and water-to-fuel injection ratios were conducted by varying the flow rate ratio from 0 to 2.0, in increments of 0.4. The results show that when the steam-to-fuel/water-to-fuel ratio was increased from 0 to 2.0, the NOx severity index dropped from 1.4267 to 0.9212 (35%) for water injection, compared to a reduction from 1.4267 to 1.045 for steam injection, which is approximately 28%. Hence, this study presents a comparative analysis of the effectiveness of steam versus water injection techniques for NOx reduction in an intercooled combined cycle gas turbine.